Mythologem of twins as a way to regenerate ethnic self-identification - Margarita I. Varfolomeeva, Elena V. Pupynina, Sergey V. Zhilyakov, Ekaterina A. Shamrina,; Genkin, Yuliana Y. (Opción, 2019)
The article investigates the interpretation and perception of twin mythologem in Old Russian literature comparative qualitative research methods. As a result, The mythologem of twins is one of important archetypal images. In this research, the twin mythologem is understood here as a regenerating agent for ethnic self-identification that becomes especially important during critical (bifurcation) periods in Russian history. In conclusion, the variants of twin mythologem discussed here combine the meanings of growth, regeneration, cultural heroes, the sacral upper part of the world, self-sacrifice.